Health-Related Quality of Life after Pediatric Liver Transplantation: A Qualitative Analysis of the Perspectives of Health Care Providers - Mar Miserachs; David B. Nicholas; Anthony R. Otley; Vicky Lee Ng (Canadian Journal of Gastroenterology and Hepatology)
With improved survival outcomes after pediatric liver transplantation (LT), health-related quality of life (HRQoL) is an important outcome metric. Understanding the elements contributing to HRQoL after LT in children would enable more targeted strategies towards optimizing best outcomes. This qualitative study aimed to explore health care providers (HCP) perceptions about HRQoL after pediatric LT. Thirteen experienced HCP participated in two focus group discussions. Data analysis via a thematic analysis approach revealed 4 major themes: “LT as a facilitator of better HRQoL,” “coping and adapting to LT,” “living with a transplanted liver,” and “the family context.” HCP identified elements that both enhance (improved physical health, peer relationship, and activities of daily living) and challenge (need for immunosuppression, transplant follow-up, and restrictions) the multidimensional domains of HRQoL. HCP perceived LT to be a stressful life-changing event for children and their families. Patients and their parents’ ability to cope and adjust positively to LT was perceived as a key contributor to better HRQoL. HCP perspective highlights the importance of promoting psychosocial support and a family-centered care delivery model towards the overarching goal of optimizing durable outcomes.